Recent Advances in Aqueous-Phase Catalytic Conversions of Biomass Platform Chemicals Over Heterogeneous Catalysts - Xiaoxian Li; Lilong Zhang; Shanshan Wang; Yulong Wu; Yulong Wu (Frontiers in Chemistry, 2020)
A series of biomass-derived platform molecules, such as glucose, furans, levulinic acid, 5-hydroxymethylfurfural, and acetic acids, can be converted into a variety of value-added chemicals through catalytic transformations that include dehydration, hydrogenation, oxidation, isomerization, reforming, ketonization, and aldol condensation over heterogeneous catalysts. Aqueous-phase processing is an important issue and a great challenge for the heterogeneous catalytic conversion of biobased chemicals due to the high water content of the biomass and the formation of water during the transformation process. In this paper, heterogeneous catalysts that are applicable to the aqueous-phase conversion process of biomass platform chemicals, including noble metal catalysts, non-noble metal catalysts, bimetallic catalysts, metal oxides, and zeolite, are introduced, and a comprehensive evaluation of the catalyst performance, including the catalytic activity, stability, and regeneration performance of different kinds of heterogeneous catalysts, are made. Besides, we highlighted the effect of water on heterogeneous catalysts and the deactivation mechanism in the aqueous phase. Beyond this, several catalytic mechanisms of aqueous-phase conversion over heterogeneous catalysts are summarized in order to help understand the reaction process on the surface of catalysts in the aqueous phase, so as to design targeted catalysts. At last, a prospect of biobased chemicals and fuels is forecasted.